MRI guides diagnostic approach for ischaemic stroke. Issue 11 (7th May 2011) - Kumar, M A; Vangala, H; Tong, D C; Campbell, D M; Balgude, A; Eyngorn, I; Beraud, A S; Olivot, J M; Hsia, A W; Bernstein, R A; Wijman, C A; Lansberg, M G; et al.
Abstract : Background and aim: Identification of ischaemic stroke subtype currently relies on clinical evaluation supported by various diagnostic studies. The authors sought to determine whether specific diffusion-weighted MRI (DWI) patterns could reliably guide the subsequent work-up for patients presenting with acute ischaemic stroke symptoms. Methods: 273 consecutive patients with acute ischaemic stroke symptoms were enrolled in this prospective, observational, single-centre NIH-sponsored study. Electrocardiogram, non-contrast head CT, brain MRI, head and neck magnetic resonance angiography (MRA) and transoesophageal echocardiography were performed in this prespecified order. Stroke neurologists determined TOAST (Trial of Org 10172 in Acute Stroke Treatment) classification on admission and on discharge. Initial TOAST stroke subtypes were compared with the final TOAST subtype. If the final subtype differed from the initial assessment, the diagnostic test deemed the principal determinant of change was recorded. These principal determinants of change were compared between a CT-based and an MRI-based classification schema. Results: Among patients with a thromboembolic DWI pattern, transoesophageal echocardiography was the principal determinant of diagnostic change in 8.8% versus 0% for the small vessel group and 1.7% for the other group (p<0.01). Among patients with the combination of a thromboembolic pattern on MRI and a negative cervical MRA, transoesophageal echocardiography led to a change in diagnosis in 12.1%. There was no significant difference between groups using a CT-based scheme. Conclusions: DWI patterns appear to predict stroke aetiologies better than conventional methods. The study data suggest an MRI-based diagnostic algorithm that can potentially obviate the need for echocardiography in one-third of stroke patients and may limit the number of secondary extracranial vascular imaging studies to approximately 10%.